Determinants of COVID-19 vaccine uptake among persons with disabilities in three selected districts of Zambia. - Allan Mayaba Mwiinde; Isaac Fwemba; Joseph Mumba Zulu; Choolwe Jacobs; Patrick Kaonga (PLOS Global Public Health)
COVID-19, is still a public health threat due to uncertainties around the potential evolution of the virus, changes in clinical characteristics, and the introduction of new prevention and therapeutic modalities. Persons with Disabilities (PWDs) were among the most highly affected groups by the COVID-19 pandemic due to their underlying conditions. This study aimed to establish the prevalence and identify the determinants of COVID-19 vaccine uptake among PWDs in three selected districts of Zambia. A cross-sectional study was conducted from June to August 2023 in Lusaka, Mazabuka, and Monze Districts. Structured questionnaires were developed and administered to PWDs aged 18 years and above. Log-binomial model was used to calculate the adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs) for assessing COVID-19 vaccine acceptance and its determinants. Out of the sample of 985, the proportion of COVID-19 vaccine uptake was 67.6% (95% CI: 65%, 71%). Vaccine uptake was higher among the married (aPR: 1.21; 95% CI:1.06, 1.39) participants from Mazabuka District (aPR: 1.61; 95% CI: 1.34, 1.93) living in rural areas (aPR:1.27; 95% CI: 1.09, 1.49) having extra income (aPR:1.27; 95% CI: 1.09,1.50) involved in routine health checkup (aPR:1.23; 95% CI: 1.11, 1.37) previously infected with COVID-19 (aPR:1.32; 95% CI, 1.04-1.68) previously vaccinated (aPR: 1.16; 95% CI: 1.00, 1.33) and understanding safety of the vaccine (aPR: 2.33; 95% CI: 1.55, 3.49). Conversely, low vaccine uptake was observed among participants earning less than k200 from social cash transfer (aPR: 0.79; 95% CI: 0.71, 0.87). More research is needed to identify determinants of vaccine uptake among PWDs that make them more vulnerable to infectious diseases such as COVID-19. There is need to improve vaccination coverage among PWDs. A more holistic and inclusive health promotion approach needs to be adopted to ensure that PWDs are not left behind in accessing vaccines.